BENEFITS AND LIMITATIONS OF ROBOTIC PERCUTANEOUS CORONARY INTERVENTION IN THE FIELD OF INTERVENTIONAL CARDIOLOGY (CIPEEX, 2025)
There are occupational dilemmas in the field of interventional cardiology that impact not only the interventional cardiologist's health but also the entire surgical team involved in the procedures. It is well known that fluoroscopy is used for real-time study of myocardial revascularization and involves the emission of X-rays to examine compromised coronary arteries in real-time. Additionally, lead aprons, which weigh more than 7 kg, can lead to potential orthopedic injuries over time. In this regard, the advent of Robotic Percutaneous Coronary Intervention (R-PCI) seems to mitigate such deleterious effects inherent to cardiac catheterization. The study aims to evaluate the benefits and limitations of R-PCI in interventional cardiology practice. This study consists of a literature review using articles published between 2019-2024 from the PubMed and Google Scholar databases. The inclusion criteria were full-text and free articles in English, while incomplete articles were excluded. Four articles were used for this review. R-PCI is gaining prominence due to its ability to increase stent placement precision and reduce occupational radiation exposure. Studies such as the PRECISE trial demonstrate success in over 97% of cases, especially in low to moderate complexity lesions. One of the main attractions of R-PCI is the reduction in radiation exposure by allowing remote control of the machine that guides the wire with balloon and stents. Additionally, the automated system enables the interventional cardiologist to operate on the patient without the need for heavy lead aprons. However, there are limitations regarding the use of this technology in patients with more complex lesions, tortuous and calcified arteries, and manual vascular access. Despite the promising potential for future advancements, including remote interventions, further studies are needed to validate the efficacy and safety of R-PCI in higher-risk patients.
Keywords: angioplasty; percutaneous coronary intervention; cardiovascular surgical procedures; robotic surgical procedures